EVALUASI KETERSEDIAAN AIR BERSIH JANGKA PANJANG MENGGUNAKAN METODE F.J. MOCK DI KECAMATAN MEDAN PETISAH - Maharani, Annisa; Zebua, Adven Tara Fowua Saro; Fathurrahman, Auliya; Siagian, Ilham Afandi; Lumban Toruan, Ruth Paula Margareth (UNIKA Santo Thomas, 2025)
Population growth and urban development have led to a significant increase in clean water demand in Medan Petisah District. This study aims to analyze the projected clean water demand and availability over the next 10, 30, and 50 years. The methods used include population projections based on arithmetic and geometric approaches, as well as water demand estimation categorized into domestic and non-domestic use, referring to national standards (SNI). The results indicate that clean water demand will continue to rise significantly, while water availability is expected to remain stable or even decline due to the degradation of water sources and increased consumption. This study recommends integrated water resource management strategies, improved distribution efficiency, and protection of raw water sources to ensure the sustainability of clean water services in the future.